(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2022)
The role of Forensic odontologist in genealogical analysis is important identification. This is useful in knowing whether someone has the same or different family lineage. Genealogical analysis can use Y-STR DNA from teeth with Amelogenin. This gene is present in hydroxyapatite crystals on the surface of enamel, dentin and tooth roots. Recent methods obtained from several literatures show that this examination can be performed using a Raman spectra technique which provides a laser wave stream during PCR analysis. The results of the conclusions from several literatures obtained good accuracy.